PENGEMBANGAN E-MODUL PROJEK PENGUATAN PROFIL PELAJAR PANCASILA FASE E PADA TEMA KEARIFAN LOKAL DAERAH BENGKULU: PENGEMBANGAN E-MODUL PROJEK PENGUATAN PROFIL PELAJAR PANCASILA FASE E PADA TEMA KEARIFAN LOKAL DAERAH BENGKULU - Vannesa Okta Andyani; Dewi Handayani; Hermansyah Amir (ALOTROP, 2024)
This research is a study and development of an e-module project to strengthen the Pancasila student profile phase E on the theme of local wisdom in the Bengkulu area. This research aims to determine the feasibility level of the e-module and the students' responses to the developed project e-module. The development of this e-module uses the ADDIE development model (Analyze, Design, Develop, and Evaluation), which is limited only to the Develop stage. The research was conducted from May to July at SMAN 1 Kota Bengkulu. The subjects of the research were 36 tenth-grade students of class X.B at SMAN 1 Kota Bengkulu. The instruments in this research were interview sheets, validation sheets, and student response questionnaires. The results of this study showed that (1) the feasibility level of the e-module had a score of 93.6% with a category of very feasible, and (2) the student response test results to the e-module obtained a score of 89.0% with a category of very good. This means that the e-module project to strengthen the Pancasila student profile phase E on the theme of local wisdom in the Bengkulu area is suitable for use.